Chloride binding of monosulfate hydrate (AFm) and its effect on steel corrosion in simulated concrete pore solution. (15th May 2023) - Zhang, Yuguo; Sun, Congtao; Zhang, Peng; Sun, Ming; Geng, Yuanjie; Zhao, Maomi; Fan, Liang; Liu, Nazhen; Duan, Jizhou
Abstract: The impact of monosulfate hydrate (AFm) on chloride (Cl − ) binding and steel corrosion in simulated concrete pore solutions (SCPSs) was evaluated. In the SCPS with AFm added, a high concentration of Cl − promoted the Cl − binding amount per unit AFm without producing Kuzel's salt. The Cl − binding capacity of AFm could be improved by appropriately changing the amount of AFm with a constant Cl − concentration. The addition of AFm to the SCPS shortened the passivation time and created a more stable passivation film of the steel. The SO4 2− produced by the AFm binding with Cl − preferentially reacted with AFm to form AFt, and it affected the stability of the Friedel's salt to release Cl − . The addition of AFm raised the chloride threshold value (CTV) for steel corrosion. However, after reaching the CTV, the corrosion rate of steels increased dramatically, due to the release of the bound Cl − . Highlights: The Cl − concentration and AFm dosage affect the binding of AFm to Cl − . The SCPS with AFm added can form a more stable passivation film of steel. The SCPS with AFm added can increase the CTV of steel. After the CTV, the corrosion rate increased dramatically due to bound Cl − release.